Shifting palliative care paradigm in primary care from better death to better end-of-life: a Swiss pilot study - Johanna Sommer; Christopher Chung; Dagmar M. Haller; Sophie Pautex (BMC, 2021)
Abstract Background Patients suffering from advanced cancer often loose contact with their primary care physician (PCP) during oncologic treatment and palliative care is introduced very late. The aim of this pilot study was to test the feasibility and procedures for a randomized trial of an intervention to teach PCPs a palliative care approach and communication skills to improve advanced cancer patients' quality of life. Methods Observational pilot study in 5 steps. 1) Recruitment of PCPs. 2) Intervention: training on palliative care competencies and communication skills addressing end-of-life issues. 3) Recruitment of advanced cancer patients by PCPs. 4) Patients follow-up by PCPs, and assessment of their quality of life by a research assistant 5) Feedback from PCPs using a semi-structured focus group and three individual interviews with qualitative deductive theme analysis. Results Eight PCPs were trained. Patient recruitment was a challenge for PCPs who feared to impose additional loads on their patients. PCPs became more conscious of their role and responsibility during oncologic treatments and felt empowered to take a more active role picking up patient's cues and addressing advance directives. They developed interprofessional collaborations for advance care planning. Overall, they discovered the role to help patients to make decisions for a better end-of-life. Conclusions While the intervention was acceptable to PCPs, recruitment was a challenge and a follow up trial was not deemed feasible using the current design but PCPs reported a change in paradigm about palliative care. They moved from a focus on helping patients to die better, to a new role helping patients to define the conditions for a better end-of-life. Trial registration The ethics committee of the canton of Geneva approved the study (2018-00077 Pilot Study) in accordance with the Declaration of Helsinki.